TFAP4 exacerbates pathological cardiac fibrosis by modulating mechanotransduction - Jie Liu; Jingjing Feng; Jingxuan Zhao; Xiangjie Kong; Zhangyi Yu; Yuanru Huang; Zechun He; Mengxin Liu; Zheng Liu; Zhibing Lu; Li Wang (Cell Insight)
Cardiac fibroblast (CF) differentiation into myofibroblasts is a crucial driver of cardiac fibrosis, leading to extensive extracellular matrix (ECM) deposition that increases myocardial stiffness and eventually impairs heart function. Mechanotransduction has merged as a key regulator of CF activation and the fibrotic response post-myocardial infarction (MI). However, the molecular mechanisms linking CF activation to mechanical cues within the injured myocardium remain poorly understood. Here we identified transcription factor TFAP4 as a central regulator of fibrosis in both human and murine models. TFAP4 overexpression enhances CF proliferation, ECM protein expression, and myofibroblast differentiation. Notably, TFAP4 directly activates expression of mechanosensors including Itga11 and Piezo2, which are essential for transmitting mechanical signals that promote CF activation and fibrosis. Silencing Itga11 and Piezo2 reverses the pro-fibrotic effects of TFAP4, while TFAP4 downregulation in vivo reduces fibrosis and improves cardiac function post-MI. These findings identify TFAP4 as a pivotal link between mechanotransduction and fibrosis, suggesting it as a potential therapeutic target to mitigate fibrosis and enhance cardiac recovery following MI.